Translations of English Children’s Literature in the Armenian Periodicals in India - Baloyan, Varduhi (Translation Studies: Theory and Practice, 2022)
Translations had a significant role both in the popularization of Eastern Armenian and the establishment of literary and cultural ties between the Armenian community and the British. The purpose was to further the international outlook, understanding and emotional experience of foreign environments and cultures, on the one hand, next was to make more literature available to children and to contribute to the development of the readers’ set of values. It should be noted that literary relations first of all contributed to the emergence of bilingual dictionaries. Shmavonian published an English-Armenian dictionary which was intended “for the entertainment of studious children” (Mkhitaryan 2016:81). 19th century was marked by social political changes and created conditions for the development of new Armenian literature which was so important for shaping the mind set and behavior of the Armenian children. Thus, Armenian translators translated literature in connection with social and economic forces. The Armenian printing business in India operated for a century and published almost 200 books, booklets and more than ten periodicals. In this article some translations published in Azdarar (The Intelligencer, 1794, Madras), Azgaser (the Patriot, 1845, Calcutta), Azgaser Araratian (Patriot Araratian, 1848. Calcutta), and Hayeli Kalkatian (Mirror of Calcutta, 1820, Calcutta) are examined.